The impacts of financial integration on the linkages between monetary independence and foreign exchange reserves - Law, Chee Hong; Tee, Chee Lip; Lau, Wei Theng (Routledge, 2019)
This paper investigates the short-run and long-run effects of financial integration on the dynamics between monetary independence and foreign exchange reserves using a GMM system estimation involving two-year non-overlapping average data (2000-2011) from 114 countries. The results indicate that the effect of foreign exchange reserves on the monetary independence is intensified by the level of financial integration. This suggests a positive spill over effect from the financial integration to the monetary policy independence. Besides, a positive implication of financial integration on monetary independence could be established when the foreign exchange reserves is at the maximum level. In addition, the comparisons between the mean of foreign exchange reserves and the threshold levels of foreign exchange reserves that neutralise the impact of financial integration indicate that on average, the foreign exchange reserves are sufficient to offset the effect of financial integration. A stable exchange rate will undermine the positive impact of foreign exchange reserves on monetary independence. Finally, the long-run and short-run impacts occur in the same direction. This paper ends with some policy implications and suggestions for future research.